Combined Salinity–Flooding Stress Reveals Wide Phenotypic Variation and Candidate Genomic Loci Associated With Survival in Rice at the Tillering Stage - Nhung Thi Hong Phan; Loc Van Nguyen; Hanh Thi Tang; Ngoc Thi Minh Tran; Hoai Thi Thu Tran; Long Viet Nguyen; Cuong Van Pham (Journal of Crop Health, 2026)

Control of anthracnose caused by Colletotrichum truncatum on dragon fruit (Hylocereus undatus) using recombinant chitinase - Le Thi Ha Thanh; Nguyen Thi Thuy Tien; Dang Van Thanh; Nguyen Thi Yen Nhi; Nguyen Quang Duc Tien; Nguyen Hoang Loc (Archives of Microbiology, 2026)

Application of thermostable chitinase I168L in the control of anthracnose on avocado and evaluation of cross-infection ability of Colletotrichum species - Le Thi Ha Thanh; Dang Van Thanh; Huynh Thi Thu Ha; Nguyen Hoang Loc (Physiological and Molecular Plant Pathology, 2026)

Madecassic acid analogues with a five-membered A-ring and their cytotoxic activity - Van Loc Tran; The Anh Nguyen; Nguyen Tran Dang; Thi Phuong Thao Tran; Tuan Anh Tran; Van Sung Tran; Van Chien Tran (Natural Product Research, 2026)

Plant-parasitic nematodes associated with dragon fruit and the first report of the cactus cyst nematode, Cactodera cacti, in the Mekong Delta, Vietnam - Loc Thanh Thi Vo; Hoa Van Nguyen; Uyen Kim Thi Dang; Tien Ngoc Thi Le; Cuong Xuan Nguyen; Koki Toyota; Sinh Van Nguyen (Australasian Plant Pathology, 2026)

Agronomic performance, grain quality, and combining ability of newly developed two-line hybrid rice lines - Tran Van Quang; Tran Thi Huyen; Do Van Duc; Tran Hoang Lan; Chu Duc Ha; Nguyen Van Loc (Vegetos, 2025)

Environmental Drivers of Quinoa Germination: Growth Responses and Machine Learning Predictions - Van Loc Nguyen; Trung Hung Nguyen; Hoai Nam Vu; Thi Hong Nhung Phan; Viet Long Nguyen; Duc Ha Chu; Daniel Bertero; Néstor Curti; Duc Trung Nguyen; Ton Viet Ta (Journal of Crop Health, 2025)

In vitro plant regeneration, callus suspension culture, and production of bioactive metabolites in dong quai (Angelica sinensis) - Phung Thi Bich Hoa; Nguyen Hoang Phuc; Ho Ngoc Phu; Nguyen Van Hoai Nam; Le Nguyen Minh Thu; Le Thi Ha Thanh; Nguyen Hoang Loc (South African Journal of Botany, 2025)

Assessing the sensitivity of physiographical parameters in modeling hydrological ecosystem services that support food security: The case of Vietnamese Mekong Delta - Sreejita Banerjee; Ho Hu Loc; Indrajit Pal; Anirban Mukhopadhyay; Thanh Van Pham Huynh; Duy Tien Pham; Hong Cam Nguyen Thi (Modeling Earth Systems and Environment, 2025)
Vietnamese Mekong Delta (VMD) experiences high soil loss and nutrient export, which in turn impacts food security and livelihood. These parameters play an important role in hydrological ecosystem services. Using the InVEST modeling software, we quantify and map sediment and nutrient regulation, as well as seasonal water yield, across the VMD. We propose an innovative approach for model validation, tailored to regions with limited data availability, that utilizes observed data to enhance the accuracy and reliability of the model. The results of this study indicate that approximately 65% of the total watershed is prone to high nutrient export, and 33% of the area is prone to soil erosion. Sensitivity analysis for the model parameters reveals that variations in k (nutrient delivery ratio, sediment delivery ratio) and β (seasonal water yield) have the most significant effects on sediment export and baseflow, respectively. This study focuses on regulating ecosystem services in agricultural regions that contribute to Vietnam’s food production. This study presents a series of implications and findings that contribute to the overall understanding of how hydrological ecosystem services can support food security in data-scarce regions, as well as offer recommendations to policymakers on the application of nature-based solutions and the sustainable management of water resources.

A new sacculatane diterpenoid and a new oplopanone sesquiterpenoid from Porella perrottetiana (Mont.) Trevis. collected in Sapa, Vietnam - Tran Van Chien; Nguyen The Anh; Tran Van Loc; Tran Van Sung; Tran Thi Phuong Thao; Vadim Bakalin; Nguyen Hung Manh; Nguyen Van Sinh (Natural Product Research, 2025)

Advanced Zr-CeO2 supported Ni catalysts for production of synthetic natural gas (SNG) from CO2 - Nguyen Tri; Nguyen Phung Anh; Do Ba Long; Ho Gia Thien Thanh; Bui Thi Hong Nhung; Nguyen Thi Thuy Van; Cam Anh Ha; Hoang Tien Cuong; Luu Cam Loc (Fuel, 2025)

Improving the thermostability of 42 kDa chitinase from Trichoderma asperellum SH16 expressed in Nicotiana benthamiana via site-directed mutagenesis - Nguyen Quang Duc Tien; Dang Van Thanh; Huynh Thi Thu Ha; Nguyen Hoang Tue; Nguyen Hoang Phuc; Phung Thi Bich Hoa; Le Thi Ha Thanh; Nguyen Hoang Loc (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Effects of fly ash application on the growth and disease resistance of peanut plants (Arachis hypogaea) cultivated in different soil types - Van Loc Nguyen; Ha Duc Chu; Duc Huy Nguyen (Vegetos, 2024)

Integrated assessment of salinity intrusion and water scarcity in Ben Tre, Mekong Delta: implications for sustainable livelihoods and adaptive water management - Thanh Tran; Do Vinh Duong; Ho Huu Loc; Vuong Nguyen Đinh; Tran Anh Trung; Van Thi Thanh Ho; Long Giang Bach; Lam Van Tan; Phung Chi Sy (Environment, Development and Sustainability, 2024)

Integration of genome-wide association studies reveal loci associated with salt tolerance score of rice at the seedling stage - Nhung Thi Hong Phan; Cuong Van Pham; Hanh Thi Tang; Loc Van Nguyen; Long Viet Nguyen; Pierre Bertin (Journal of Applied Genetics, 2023)

Effective adsorption of Pb(II) ion from aqueous solution onto ZSM-5 zeolite synthesized from Vietnamese bentonite clay - Ngoc-An Nguyen; Duy-Khoi Nguyen; Van-Phuc Dinh; Bich-Ngoc Duong; Loc Ton-That; Nguyen Trong Hung; Thien-Hoang Ho (Environmental Monitoring and Assessment, 2023)

Kinetic studies of the removal of methylene blue from aqueous solution by biochar derived from jackfruit peel - Loc Ton-That; Thi-Ngoc-Linh Huynh; Bich-Ngoc Duong; Duy-Khoi Nguyen; Ngoc-An Nguyen; Van-Hien Pham; Thien-Hoang Ho; Van-Phuc Dinh (Environmental Monitoring and Assessment, 2023)

Genetic diversity and genetic analysis for pigmented pericarps in rice (Oryza sativa L.) - Tran Van Quang; Nguyen Van Loc; Nguyen Quoc Trung; Tran Thi Huyen; Le Van Huy; Ngo Thi Hong Tuoi (Vegetos, 2023)

Germination responses to seed-rhizosphere hypoxia in relation to waterlogging tolerance of soybean - Loc Van Nguyen; Luong Thanh Le; Thai Hoang Dinh; Thanh Tuan Nguyen; Hang Thi Thuy Vu; Ha Duc Chu; Viet Long Nguyen (Vegetos, 2023)

A newly constructed Agrobacterium-mediated transformation system based on the hisB auxotrophic marker for genetic manipulation in Aspergillus niger - Hanh-Dung Thai; Loc Thi Binh Xuan Do; Xuan Thi Nguyen; Tao Xuan Vu; Huyen Thi Thanh Tran; Huy Quang Nguyen; Van-Tuan Tran (Archives of Microbiology, 2023)

Recovery from drought and saline stress in growth and physiology of sugarcane - Thai-Hoang Dinh; Hoang-Minh-Oanh Pham; Van-Loc Nguyen; Ngoc-Thang Vu (Vegetos, 2023)

Roles of root plasticity to growth, water uptake and yield of quinoa under water regimes - Thi Ngoc Dinh Nguyen; Hong Hanh Nguyen; Van Loc Nguyen (Vegetos, 2022)

Epistemic community in transboundary river regime: a case study in the Mekong River Commission regarding mainstream hydropower development - Tang Luu; Erik van Slobbe; Jos Timmerman; Loc Huu Ho; Tran Duc Dung; Chau Nguyen Xuan Quang (Environmental Monitoring and Assessment, 2022)

Effect of growth promoter VIUSID® on performance of fodder maize under different levels of nitrogen - Loc Van Nguyen; Duc Anh Nguyen; Hoang Thai Dinh; Mbaraka Saidi Rumanzi; Viet Long Nguyen (Vegetos, 2022)

Two new glycosides, farnesyl pentaglycoside and oleanane triglycoside from Lepisanthes rubiginosa , a mangrove plant collected from Thua Thien-Hue province, Vietnam - Loc Van Tran; Ninh Pham Thi; Luu Nguyen Thi; Chien Van Tran; Nhu Thi Quynh Vo; Anh Ngoc Ho; Viet Cong Do; Van Sung Tran; Thao Thi Phuong Tran (Natural Product Research, 2022)

The effects of substrates on growth and green coverage of Blue daze (Evolvulus glomeratus) under rooftop condition - Anh Duc Nguyen; Ha Duc Chu; Van Loc Nguyen (Vegetos, 2022)

Intensified salinity intrusion in coastal aquifers due to groundwater overextraction: a case study in the Mekong Delta, Vietnam - Dang An Tran; Maki Tsujimura; Hai V. Pham; Tam V. Nguyen; Loc Huu Ho; Phu Le Vo; Khai Quang Ha; Thanh Duc Dang; Doan Van Binh; Quang-Van Doan (Environmental Science and Pollution Research, 2022)

Chevalierinol A and B, two new neolignan sesquiterpenoids from Magnolia chevalieri - Pham Thi Ninh; Chu Thi Thu Ha; Tran Huy Thai; Nguyen Phuong Hanh; Nguyen Sinh Khang; Nguyen Thi Dung; Ly Thi Thu Hoai; Tran Van Chien; Tran Van Loc; Vo Thi Quynh Nhu; Nguyen The Anh; Trieu Quy Hung; et al. (Natural Product Research, 2021)

A new phenolic acid from the wood of Mangifera gedebe - Hai Xuan Nguyen; Loc Thanh Nguyen; Truong Nhat Van Do; Tho Huu Le; Phu Hoang Dang; Hung Manh Tran; Nhan Trung Nguyen; Mai Thanh Thi Nguyen (Natural Product Research, 2021)

Near-isogenic lines of soybean confirm a QTL for seed waterlogging tolerance at different temperatures - Van Loc Nguyen; Thi Thu Hien Dang; Ha Duc Chu; Tetsuhiro Nakamura; Tomomi Abiko; Toshihiro Mochizuki (Euphytica, 2021)

Variation in root growth responses of sweet potato to hypoxia and waterlogging - Loc Van Nguyen; Tri Manh Le; Phuong Diep Vien Ta; Giang Hoai Tran; Mbaraka Saidi Rumanzi; Hanh Thi Tang; Long Viet Nguyen (Vegetos, 2020)

Synthesis of dammarenolic acid derivatives with a potent α-glucosidase inhibitory activity - Irina E. Smirnova; Anastasiya V. Petrova; Oxana B. Kazakova; El’za M. Minnibaeva; Alexandra A. Fedorova; Loc Tran Van; Chien Tran Van; Ninh Pham Thi; Thao Tran Thi Phuong; Dung Nguyen Thi; Ha Thi Thu Nguyen (Medicinal Chemistry Research, 2020)

Two new prenylated isoflavones from Maclura cochinchinensis collected in Hoa Binh province Vietnam - Tran Van Chien; Nguyen The Anh; Nguyen Tuan Thanh; Tran Thi Phuong Thao; Tran Van Loc; Tran Van Sung (Natural Product Research, 2019)

Synthesis of asiatic acid derivatives and their cytotoxic activity - Loc Tran Van; Quynh Nhu Vo Thi; Chien Tran Van; Phuong Thao Tran Thi; Ninh Pham Thi; Thanh Nguyen Tuan; Thu Ha Le Thi; Nga Nguyen Thi; Thao Do Thi; Sung Tran Van (Medicinal Chemistry Research, 2018)

A new and efficient approach for construction of uridine/uracil auxotrophic mutants in the filamentous fungus Aspergillus oryzae using Agrobacterium tumefaciens-mediated transformation - Khuyen Thi Nguyen; Quynh Ngoc Ho; Loc Thi Binh Xuan Do; Linh Thi Dam Mai; Duc-Ngoc Pham; Huyen Thi Thanh Tran; Diep Hong Le; Huy Quang Nguyen; Van-Tuan Tran (World Journal of Microbiology and Biotechnology, 2017)

Mapping quantitative trait loci for root development under hypoxia conditions in soybean (Glycine max L. Merr.) - Loc Van Nguyen; Ryoji Takahashi; Stephen Mwangi Githiri; Tito O. Rodriguez; Nobuko Tsutsumi; Sayuri Kajihara; Takasi Sayama; Masao Ishimoto; Kyuya Harada; Keisuke Suematsu; Tomomi Abiko; Toshihiro Mochizuki (Theoretical and Applied Genetics, 2017)

In vivo evaluation of transgenic watercress containing gene encoding Escherichia coli heat-labile toxin B subunit - Nguyen Hoang Loc; Nguyen Van Song; Dang Thanh Long; Tae-Geum Kim; Moon-Sik Yang (Journal of Plant Biochemistry and Biotechnology, 2015)

Expression of the Escherichia coli heat-labile enterotoxin B subunit in transgenic watercress (Nasturtium officinale L.) - Nguyen Hoang Loc; Nguyen Van Song; Nguyen Quang Duc Tien; Tang Thuy Minh; Phan Thi Quynh Nga; Tae-Geum Kim; Moon-Sik Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)